Phylogenetic evidence of the intercontinental circulation of a Canine distemper virus lineage in the Americas (2023)
Canine distemper virus (CDV) is the cause of a multisystem disease in domestic dogs and wild animals, infecting more than 20 carnivore and non-carnivore families and even infecting human cell lines in in vitro conditions.